Peroxisome-Derived Hydrogen Peroxide Modulates the Sulfenylation Profiles of Key Redox Signaling Proteins in Flp-In T-REx 293 Cells - Lismont, Celien; Revenco, Iulia; Li, Hongli; Costa, Cláudio F.; Lenaerts, Lisa; Hussein, Mohamed A. F.; De Bie, Jonas; Knoops, Bernard; Van Veldhoven, Paul P.; Derua, Rita; Fransen, Marc (Frontiers in Cell and Developmental Biology, 2022)
The involvement of peroxisomes in cellular hydrogen peroxide (H2O2) metabolism has been a central theme since their first biochemical characterization by Christian de Duve in 1965. While the role of H2O2 substantially changed from an exclusively toxic molecule to a signaling messenger, the regulatory role of peroxisomes in these signaling events is still largely underappreciated. This is mainly because the number of known protein targets of peroxisome-derived H2O2 is rather limited and testing of specific targets is predominantly based on knowledge previously gathered in related fields of research. To gain a broader and more systematic insight into the role of peroxisomes in redox signaling, new approaches are urgently needed. In this study, we have combined a previously developed Flp-In T-REx 293 cell system in which peroxisomal H2O2 production can be modulated with a yeast AP-1-like-based sulfenome mining strategy to inventory protein thiol targets of peroxisome-derived H2O2 in different subcellular compartments. By using this approach, we identified more than 400 targets of peroxisome-derived H2O2 in peroxisomes, the cytosol, and mitochondria. We also observed that the sulfenylation kinetics profiles of key targets belonging to different protein families (e.g., peroxiredoxins, annexins, and tubulins) can vary considerably. In addition, we obtained compelling but indirect evidence that peroxisome-derived H2O2 may oxidize at least some of its targets (e.g., transcription factors) through a redox relay mechanism. In conclusion, given that sulfenic acids function as key intermediates in H2O2 signaling, the findings presented in this study provide valuable insight into how peroxisomes may be integrated into the cellular H2O2 signaling network.